2018
DOI: 10.1364/boe.9.006205
|View full text |Cite
|
Sign up to set email alerts
|

Retinal optical coherence tomography image enhancement via deep learning

Abstract: Optical coherence tomography (OCT) images of the retina are a powerful tool for diagnosing and monitoring eye disease. However, they are plagued by speckle noise, which reduces image quality and reliability of assessment. This paper introduces a novel speckle reduction method inspired by the recent successes of deep learning in medical imaging. We present two versions of the network to reflect the needs and preferences of different end-users. Specifically, we train a convolution neural network to denoise cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…Advances in the diagnosis and understanding of the DME disease have been made in the recent decades [6], including the proposal of new therapies besides macular laser therapy. Also, retinal image analysis using Optical Coherence Tomography (OCT) scans became popular for the pathological DME identification [7] and characterization using both traditional classification techniques [8] or more novel ones, such as deep learning strategies [9,10]. Research in these scenarios contributes to the improvement of diagnosis, prognosis and monitoring tasks of the DME disease.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the diagnosis and understanding of the DME disease have been made in the recent decades [6], including the proposal of new therapies besides macular laser therapy. Also, retinal image analysis using Optical Coherence Tomography (OCT) scans became popular for the pathological DME identification [7] and characterization using both traditional classification techniques [8] or more novel ones, such as deep learning strategies [9,10]. Research in these scenarios contributes to the improvement of diagnosis, prognosis and monitoring tasks of the DME disease.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly, the GAN network contains a generative network to produce an image and a discriminator network to estimate the quality of the image produced by the generator. A variation of this architecture, called Wasserstein generative adversarial network (WGAN), which uses Wasserstein distance as a loss function, was recently utilized for resolution enhancement of OCT images . An alternative, edge‐sensitive conditional generative adversarial network (cGAN) was reported efficient against speckle noise.…”
Section: Deep Learning For Biophotonic Imagingmentioning
confidence: 99%
“…DL based algorithms have recently surpassed the performance of conventional methods in noise reduction tasks [27][28][29][30][31][32][33][34], and the applications of DL based algorithm to retinal layer segmentation have been reported [35][36][37][38][39]. Recent studies utilizing DL models for OCT image noise reduction have shown promising results [40,41]. However, to train the deep learning models, they all rely on paired images where one image is noisy and the other one is noise-reduced.…”
Section: Enhanced Oct Image Visualization Through Deep Learning Basedmentioning
confidence: 99%
“…In previous studies, n ranges from 6 to 60 [40,41]. With the current commercially available high-speed swept-source OCT devices such as the Triton OCT device that is operated at 100 kHz/sec, it is able to capture and average 128 repeated scans at a single location.…”
Section: Enhanced Oct Image Visualization Through Deep Learning Basedmentioning
confidence: 99%